2016
DOI: 10.1093/mnras/stw2262
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of selected variability detection techniques in photometric time series data

Abstract: Photometric measurements are prone to systematic errors presenting a challenge to lowamplitude variability detection. In search for a general-purpose variability detection technique able to recover a broad range of variability types including currently unknown ones, we test 18 statistical characteristics quantifying scatter and/or correlation between brightness measurements. We compare their performance in identifying variable objects in seven time series data sets obtained with telescopes ranging in size from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
99
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 173 publications
0
99
0
1
Order By: Relevance
“…Taking into account the heterogeneous nature of the input HSC v3 data, we tested various statistical indicators of variability ("variability indices", Section 1.2), which characterize the overall scatter of measurements in a light curve and/or degree of correlation between consecutive flux measurements. Sokolovsky et al (2017b) presented a detailed description and comparison of 18 variability indices proposed in the literature. These indices were tested on seven diverse sets of groundbased photometric data containing a large number of known variables.…”
Section: Algorithm For Detecting Candidate Variablesmentioning
confidence: 99%
“…Taking into account the heterogeneous nature of the input HSC v3 data, we tested various statistical indicators of variability ("variability indices", Section 1.2), which characterize the overall scatter of measurements in a light curve and/or degree of correlation between consecutive flux measurements. Sokolovsky et al (2017b) presented a detailed description and comparison of 18 variability indices proposed in the literature. These indices were tested on seven diverse sets of groundbased photometric data containing a large number of known variables.…”
Section: Algorithm For Detecting Candidate Variablesmentioning
confidence: 99%
“…The interquartile range (IQR - Kim et al 2014) is also included in our analysis since it was reported as one of the best statistical parameters to select variable stars (Sokolovsky et al 2017). The IQR uses the inner 50% of measurements, excluding the 25% brightest and 25% faintest flux measurements, i.e.…”
Section: Even Interquartile Rangementioning
confidence: 99%
“…von Neumann 1941(e.g. von Neumann , 1942Welch & Stetson 1993;Stetson 1996;Enoch et al 2003;Kim et al 2014;Sokolovsky et al 2017). Current techniques of data processing can be improved considerably.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations